2023
DOI: 10.1037/law0000389
|View full text |Cite
|
Sign up to set email alerts
|

A critical discussion of youth Miranda waivers, racial inequity, and proposed policy reforms.

Abstract: Courts often assume that youth and adult suspects are equally capable of making decisions about whether to talk to police officers—decisions that carry serious long-term consequences. In Miranda v. Arizona, the Supreme Court ruled that prior to custodial interrogation, police officers must remind suspects of their rights to silence and legal counsel, and a suspect must waive their rights “voluntarily, knowingly, and intelligently” for police to continue questioning. This legal standard was extended to youth wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…This number significantly increased when the crime severity was moderate (85.1% advised rights assertion, odds ratio, OR = 1.58) and when it was high (88% advised rights assertion, OR = 2.12). Police legitimacy and interrogation knowledge were significant predictors of parents’ predicted Miranda advice; analyses with these variables are reported elsewhere (Baker et al, in press).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This number significantly increased when the crime severity was moderate (85.1% advised rights assertion, odds ratio, OR = 1.58) and when it was high (88% advised rights assertion, OR = 2.12). Police legitimacy and interrogation knowledge were significant predictors of parents’ predicted Miranda advice; analyses with these variables are reported elsewhere (Baker et al, in press).…”
Section: Resultsmentioning
confidence: 99%
“…For example, because the majority of participants in our sample were White, we were limited in our ability to explore the important influence of racial identity on parents’ perceptions of potential consequences. In a separate article, we previously reported the analyses that were possibly related to race in this sample (Baker et al, in press), which showed that, for Black and White parents, the advice parents would give their children regarding their Miranda rights differed based on parents’ racial identities and were mediated by their views of police legitimacy. It is well-established that communities of color face disadvantages at all steps of the criminal justice process (Haney-Caron & Fountain, 2021; Kutateladze et al, 2014) and, as a result, parents of color are more likely to prepare their children to have negative interactions with the police (April et al, 2022; Brunson & Weitzer, 2011).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Most individuals have only a limited understanding of their rights to remain silent and avoid self-incrimination (for a review see Rendall & MacMahon, 2021). Because of their youth, immaturity, and lack of experience with the law, adolescents seem to struggle more than adults to understand and appreciate the meaning of rights (e.g., Baker et al, 2023) and younger adolescents have a poorer understanding than older adolescents (Freedman et al, 2014). Delinquent boys who are characterized by lower psychosocial maturity showed even poorer comprehension of their rights (Colwell et al, 2005), although errors are common regardless of maturity levels (Hughes et al, 2013, Rogers et al, 2014.…”
Section: Informing Young Suspects Of Their Rightsmentioning
confidence: 99%
“…The vulnerabilities associated with adolescence are compounded when the youth belongs to a minoritized racial group, which may result in an increased risk of Miranda waiver for youth of color (Baker et al, 2023). Stereotype threat, a phenomenon in which an individual modifies their behavior due to concerns about confirming negative stereotypes about the group to which they belong (Steele & Aronson, 1995), can increase a youth’s cognitive load, in turn, impairing comprehension of legal concepts such as the Miranda warnings (Davis et al, 2013).…”
Section: Youth Miranda Waivermentioning
confidence: 99%